2021
DOI: 10.1021/acscatal.1c02698
|View full text |Cite
|
Sign up to set email alerts
|

Switching an Artificial P450 Peroxygenase into Peroxidase via Mechanism-Guided Protein Engineering

Abstract: Exploring the catalytic promiscuity of enzymes is a longstanding challenge and a current topic of interest. Our group previously modified a cytochrome P450BM3 monooxygenase to perform peroxygenase activity with assistance from a rationally designed dual-functional small molecule (DFSM). However, the DFSM-facilitated P450-H2O2 system showed limited peroxidase activity. On the basis of a mechanistic analysis of the possible competitive oxidation pathways, the present work applies a protein engineering strategy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…In more recent studies, the effect of DFSM ( i. e ., Im‐C6‐Phe) on P450BM3 enzyme activity and enantioselectivities to synthesize ( R )‐styrene oxide has been further optimized by combination with enzyme engineering [78] . With the DFSM strategy, different P450BM3 variants displayed high O ‐demethylation on aromatic ethers [79] and peroxidase activity on guaiacol, 2,6‐dimethoxyphenol, o ‐phenylenediamine, and p ‐phenylenediamine [80] . Based the crystal structure of the P450BM3‐F87A mutant in complex with Im‐C6‐Phe and NH 2 OH, multiple polar interactions and hydrophobic interactions were identified between the enzyme and the anchor group of DFSM (Figure 9B) [81] .…”
Section: Small Molecule Auxiliaries To Control P450s’ Activity For Sy...mentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent studies, the effect of DFSM ( i. e ., Im‐C6‐Phe) on P450BM3 enzyme activity and enantioselectivities to synthesize ( R )‐styrene oxide has been further optimized by combination with enzyme engineering [78] . With the DFSM strategy, different P450BM3 variants displayed high O ‐demethylation on aromatic ethers [79] and peroxidase activity on guaiacol, 2,6‐dimethoxyphenol, o ‐phenylenediamine, and p ‐phenylenediamine [80] . Based the crystal structure of the P450BM3‐F87A mutant in complex with Im‐C6‐Phe and NH 2 OH, multiple polar interactions and hydrophobic interactions were identified between the enzyme and the anchor group of DFSM (Figure 9B) [81] .…”
Section: Small Molecule Auxiliaries To Control P450s’ Activity For Sy...mentioning
confidence: 99%
“…[78] With the DFSM strategy, different P450BM3 variants displayed high O-demethylation on aromatic ethers [79] and peroxidase activity on guaiacol, 2,6-dimethoxyphenol, o-phenylenediamine, and pphenylenediamine. [80] Based the crystal structure of the P450BM3-F87A mutant in complex with Im-C6-Phe and NH 2 OH, multiple polar interactions and hydrophobic interactions were identified between the enzyme and the anchor group of DFSM (Figure 9B). [81] The computational study demonstrated that the H 2 O 2 maintained a strong H-bonding network with a bridging water and the imidazolyl group of the DFSM, which speeds up the Cpd I formation via a favored heterolytic OÀ O cleavage pathway, thus to affect the overall kinetics.…”
Section: Novel Small Molecule Auxiliariesmentioning
confidence: 99%
“…Interestingly, the oxidation of guaiacol, a classical substrate of peroxidases [141][142][143][144], catalyzed by the DFSM-facilitated P450BM3-H 2 O 2 system yielded demethylated catechol as a major product, suggesting it mainly functioned as a peroxygenase but not as a peroxidase [94]. After carefully analyzing the catalytic mechanism of the potential competitive oxidation pathways in the DFSM-facilitated P450BM3-H 2 O 2 system, Ma et al hypothesized that mutation of redox-sensitive residues may enable switching of peroxygenase activity to peroxidase activity [145]. Using a semi-rational design approach, similar to FRISM (focused rational iterative site-specific mutagenesis) named by Reetz and Wu [146,147], Ma et al identified mutations of three key redox-sensitive tyrosine residues that are located on the surface of P450.…”
Section: Switching Peroxidase Activity Of the Dfsm-facilitated P450 P...mentioning
confidence: 99%
“…This suggests that protein engineering of the DFSM-facilitated P450 peroxygenase system may also have its own unique advantages for controlling reaction selectivity in comparison with natural NADPH-dependent P450s. In addition, the high peroxidase activity of the DFSM-facilitated P450-system developed recently expanded the catalytic promiscuity of the system [145], whose further application in organic transformation is expected.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…By mimicking the molecular structure and catalytic mechanism of natural peroxygenase and peroxidase [ 32 , 33 ], we recently developed a unique P450–H 2 O 2 system by employing an exogenous fatty acyl amino acid equipped with a terminal imidazolyl (called a dual-functional small molecule, DFSM) to activate the peroxide-shunt pathway of P450BM3. The typical DFSM, such as N -(ω-imidazolyl)-hexanoyl-l-phenylalanine (Im-C6-Phe), was thought to bind with P450BM3 by the acyl amino acid, as the anchor group and its imidazolyl moiety serves as the acid–base catalyst to facilitate H 2 O 2 activation (shown as the red arrow pathway in Figure 1 A) [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. This system uses various P450BM3 variants to efficiently catalyze a variety of monooxygenation and oxidation reactions towards non-native substrates, e.g., styrene epoxidation, thioanisole sulfoxidation, hydroxylation of alkanes and aromatic compounds, demethylation of aromatic ethers, as well as one-electron oxidation of phenol and aromatic amines ( Figure 1 B).…”
Section: Introductionmentioning
confidence: 99%